Ethics, Regulation, and Biomedical Research - Weed, Matthew (Kennedy Institute of Ethics journal, 2004)
, Controversy has surrounded the institutions that facilitate discussion and regulation of American biomedical research for years. Recent challenges to the legitimacy of the President's Council on Bioethics have been focused on stem cell research. These arguments represent an opportunity to reconsider the legislation under which stem cell research is regulated, as well as to consider preexisting bodies like the Recombinant DNA Advisory Committee and National Bioethics Advisory Commission. This paper proposes a Federal Life Sciences Policy Commission, a novel commission with advisory and regulatory powers that would benefit from the positive and negative lessons learned under the legislation that currently shapes the formation and institutional characteristics of advisory bodies in the United States. The Federal Life Sciences Policy Commission would have institutional independence not present in previous advisory bodies, while maintaining the tradition of broad societal representation and thoughtful discourse that has developed in the United States.